An Electrochemically Synthesized Nanoporous Copper Microsensor for Highly Sensitive and Selective Determination of Glyphosate. Issue 7 (14th February 2020) - Regiart, Matias; Kumar, Abhishek; Gonçalves, Josué M.; Silva Junior, Gilberto J.; Masini, Jorge César; Angnes, Lúcio; Bertotti, Mauro
Abstract: A nanoporous copper (NPC) film was electrodeposited on a copper microelectrode, and the generated platform was investigated for electrochemical sensing of glyphosate (Glyp). The as‐deposited NPC film was highly pure and crystalline according to results of energy dispersive spectroscopy and X‐ray diffraction experiments, respectively. Scanning electron microscopy images confirm the NPC films possess a highly porous morphology containing dendrite fractals, and the electrodeposition parameters, particularly potential ( E d ) and time ( t d ), exert a remarkable influence on the structure of the films. Such changes in the NPC morphology with E d and t d were also correlated with the electrochemical behavior investigated by cyclic voltammetry. In the presence of Glyp, the anodic oxidation is facilitated because copper ions diffuse easily through the pores of the NPC film and form a complex with the analyte at the electrode interface. On the other hand, as the amount of copper oxides decreases due to the formation of soluble Cu(II) complex with Glyp, less current is obtained during the reverse scan, allowing a relationship between the decrease in the cathodic current and the Glyp concentration to be established. The optimized NPC‐modified Cu microelectrode showed very high sensitivity (14 nA nmol −1 L), low detection limit (4 nmol L −1 ), excellent reproducibility, and selective response for Glyp. The applicability of the sensor was demonstrated by detecting Glyp in river water samples. Abstract : River analysis : The surface of a copper disc microelectrode is modified by using the dynamic hydrogen bubble template (DHBT) method, and relevant parameters such as deposition time and deposition potential are systematically optimized. The available information on the film property and structure is correlated with the studied electrodeposition parameters. The proposed platform is successfully employed for highly sensitive electrochemical detection of glyphosate in river water samples.